2020
DOI: 10.1111/jcpp.13275
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Perspective: Adolescents’ fragile sleep—shining light on a time of risk to mental health

Abstract: As many other facets of life—biological, behavioral, psychological, cognitive, and social—undergo change during adolescence, so too does sleep. The context of sleep behavior is modified by alterations to underlying bioregulatory processes that challenge sleep’s timing, regularity, and quantity. The buildup of sleep pressure during the day gets slower, opening the door for youth to stay awake later; however, the amount of sleep required does not diminish. Further, the circadian timing system delays, again provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, although children showed a mild worsening in sleep quality, the rate of potential disturbed sleep did not increase significantly, as we observed in pre-schoolers (Di Giorgio et al, 2020). The potential risk for incurring in poor sleep due to the home confinement may have been attenuated by the later sleep timing, more aligned with the biological clock of older/pre-puberal children (Carskadon & Barker, 2020). Moreover, the change in children' sleep quality was associated with their mothers' difficulties in regulating their emotions.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Interestingly, although children showed a mild worsening in sleep quality, the rate of potential disturbed sleep did not increase significantly, as we observed in pre-schoolers (Di Giorgio et al, 2020). The potential risk for incurring in poor sleep due to the home confinement may have been attenuated by the later sleep timing, more aligned with the biological clock of older/pre-puberal children (Carskadon & Barker, 2020). Moreover, the change in children' sleep quality was associated with their mothers' difficulties in regulating their emotions.…”
Section: Discussionmentioning
confidence: 46%
“…The pandemic outbreak, imposing a prolonged and unexpected interruption of the normal school routine, daily activities, and connections with peers, could represent an important risk factor for physical and mental health in children and families. Sleep seemed to be a crucial joining link between physical and psychological wellbeing, especially for younger individuals (Becker & Gregory, 2020;Carskadon & Barker, 2020;Gregory & O'Connor, 2002). For instance, sleep duration in school-age children is negatively correlated with behavior and mood problems (Paavonen et al, 2009) and both sleep and timing modulate the children's abilities to adequately regulate emotions (Carskadon & Barker, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 , 28 ] Biological, psychosocial, and societal factors contribute to pediatric sleep and its disruption. [ 29 , 30 ] Psychosocial factors, such as use of devices with screens[ 31–33 ] and increased autonomy[ 34 , 35 ] can exacerbate the biological tendency for delayed sleep in adolescence[ 36–38 ] and increase the likelihood that insufficient sleep is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Several large population cohort studies have reported that sleep problems during childhood predict psychotic experiences in teenage years (Fisher et al, 2014; Morales-Muñoz et al, 2020; Thompson et al, 2015). Furthermore, as in adults, sleep problems in children are linked to a wide range of other negative mental and physical health outcomes (Carskadon & Barker, 2020; Dong et al, 2019; Gregory & Sadeh, 2012; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%